Glucocorticoid Receptor Function and Cognitive Performance in Women With HIV. Issue 8 (20th October 2022) - Rubin, Leah H.; Bekhbat, Mandakh; Turkson, Susie; Mehta, C. Christina; Maki, Pauline M.; Anastos, Kathryn; Gustafson, Deborah; Spence, Amanda B.; Milam, Joel; Chow, Felicia C.; Weber, Kathleen; Springer, Gayle; et al.
ABSTRACT: Objective: Alterations in glucocorticoid receptor (GCR) function may be a risk factor for cognitive complications among older people with human immunodeficiency virus (HIV). We evaluated whether HIV serostatus and age modify the GCR function-cognition association among women. Methods: Eighty women with HIV ( n = 40, <40 years of age [younger]; n = 40, >50 years of age [older]) and 80 HIV-uninfected women ( n = 40 older, n = 40 younger) enrolled in the Women's Interagency HIV Study completed a comprehensive neuropsychological test battery. Peripheral blood mononuclear cells collected concurrent with neuropsychological testing were assessed for GCR function. Multivariable linear regression analyses were conducted to examine whether a) HIV serostatus and age were associated with GCR function, and b) GCR function-cognition associations are moderated by HIV serostatus and age adjusting for relevant covariates. Results: Among older women, higher baseline FKBP5 expression level was associated with lower attention/working memory performance among women with HIV ( B = 6.4, standard error = 1.7, p = .0003) but not in women without HIV infection ( B = −1.7, standard error = 1.9, p = .37). There were no significant HIV serostatus by age interactions on dexamethasone (DEX)-stimulated expression of the genes regulated by the GCR or lipopolysaccharide-stimulated tumor necrosis factor α levels (with or without DEX stimulation; p values > .13). HIV serostatus was associated with GC target genes PER1 ( p = .006) and DUSP1 ( p = .02), but not TSC22D3 ( p = .32), after DEX stimulation. Conclusions: Collectively, these data suggest that HIV serostatus and age may modify the influence of the GCR, such that the receptor is likely engaged to a similar extent, but the downstream influence of the receptor is altered, potentially through epigenetic modification of target genes.